2006
DOI: 10.1682/jrrd.2005.11.0171
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual training improves syllable identification in new and experienced hearing aid users

Abstract: Abstract-We assessed the effects of perceptual training of syllable identification in noise on nonsense syllable test (NST) performance of new (Experiment 1) and experienced (Experiment 2) hearing aid (HA) users with sensorineural hearing loss. In Experiment 1, new HA users were randomly assigned to either immediate training (IT) or delayed training (DT) groups. IT subjects underwent 8 weeks of at-home syllable identification training and in-laboratory testing, whereas DT subjects underwent identical in-labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(101 citation statements)
references
References 61 publications
5
91
1
2
Order By: Relevance
“…For example, Ferguson and KewleyPort found that patients with mild SNHL accurately identified 73 percent of vowels at speech-to-babble ratios of -3 dB, i.e., well below typical SeRTs [8]. As a result, improving consonant comprehension is a major focus of current research on hearing aid design [9][10][11] and adaptive perceptual training [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ferguson and KewleyPort found that patients with mild SNHL accurately identified 73 percent of vowels at speech-to-babble ratios of -3 dB, i.e., well below typical SeRTs [8]. As a result, improving consonant comprehension is a major focus of current research on hearing aid design [9][10][11] and adaptive perceptual training [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Stecker et al (2006) found that the performance of older participants on a nonsense syllable test was significantly poorer than younger participants but that the degree of improvement from pre to post-training was generally greater in the older group (although not statistically significant). These findings raise questions about the possible impact of patient age (and other factors) on amount of AT benefit and therefore needs addressing in future.…”
Section: Further Examination On Patient Characteristicsmentioning
confidence: 75%
“…Some authors also use terms such as "listening training" (Tremblay et al, 1997) or "perceptual training" (Stecker et al, 2006;Woods & Yund, 2007) to describe a process of AT. Regardless of the terminology used, the listening tasks generally include lists of sentences, words or speech syllables presented in noise (background babble).…”
Section: Types Of Atmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing evidence that computer-based auditory training is beneficial and can be accomplished in the hearing clinic or at home (Burk and Humes, 2007;Burk and Humes, 2008;Burk et al, 2006;Fu, 2007;Miller et al, 2004;Miller et al, 2005;Miller, et al, 2007, Stecker et al, 2006Sweetow and Henderson-Sabes, 2004;Sweetow and Palmer, 2006;Sweetow and Sabes, 2006). SPATS was developed over approximately the same time span as many of the cited papers, but differs from them in the level of detail of the assessment component and in the kinds of training regimes available.…”
Section: Introductionmentioning
confidence: 99%